A longitudinal meta-analysis of corruption in international business and trade: Bridging the isolated themes. Issue 5 (20th October 2018) - Kouznetsov, Alex; Kim, Sarah; Pierce, Justin
ABSTRACT: This article chronicles the academic debate on corruption in international business and trade. It identifies three themes: contributing factors, consequences, and combating corruption. We found convergence in the literature and that authors tend to remain loyal to their chosen theme. As a result, we found a distressing dearth of research that transcends, integrates, or validates the interrelationships between them. Through our work, we propose the bridging of themes, demonstrating how they interrelate, thereby validating their interdependencies and the broader lens needed through which to observe corruption in international business.